Zinc-substituted Desulfovibrio gigas desulforedoxins: Resolving subunit degeneracy with nonsymmetric pseudocontact shifts - Goodfellow, Brian J. (Cold Spring Harbor Laboratory Press, 2002)
Desulfovibrio gigas desulforedoxin (Dx) consists of two identical peptides, each containing one [Fe-4S] center per monomer. Variants with different iron and zinc metal compositions arise when desulforedoxin is produced recombinantly from Escherichia coli. The three forms of the protein, the two homodimers [Fe(III)/Fe(III)]Dx and [Zn(II)/Zn(II)]Dx, and the heterodimer [Fe(III)/Zn(II)]Dx, can be separated by ion exchange chromatography on the basis of their charge differences. Once separated, the desulforedoxins containing iron can be reduced with added dithionite. For NMR studies, different protein samples were prepared labeled with (15)N or (15)N + (13)C. Spectral assignments were determined for [Fe(II)/Fe(II)]Dx and [Fe(II)/Zn(II)]Dx from 3D (15)N TOCSY-HSQC and NOESY-HSQC data, and compared with those reported previously for [Zn(II)/Zn(II)]Dx. Assignments for the (13)C(α) shifts were obtained from an HNCA experiment. Comparison of (1)H–(15)N HSQC spectra of [Zn(II)/Zn(II)]Dx, [Fe(II)/Fe(II)]Dx and [Fe(II)/Zn(II)]Dx revealed that the pseudocontact shifts in [Fe(II)/Zn(II)]Dx can be decomposed into inter- and intramonomer components, which, when summed, accurately predict the observed pseudocontact shifts observed for [Fe(II)/Fe(II)]Dx. The degree of linearity observed in the pseudocontact shifts for residues ≥8.5 Å from the metal center indicates that the replacement of Fe(II) by Zn(II) produces little or no change in the structure of Dx. The results suggest a general strategy for the analysis of NMR spectra of homo-oligomeric proteins in which a paramagnetic center introduced into a single subunit is used to break the magnetic symmetry and make it possible to obtain distance constraints (both pseudocontact and NOE) between subunits.